Optimus – Optimal Approach to Prevention of Conflict With the Law of Children and Youth - Hrnčić, Jasna; Džamonja-Ignjatović, Tamara; Despotović-Stanarević, Vera (Zbornik Instituta za kriminološka i sociološka istraživanja, 2010)
Based on current scientific research, effective global practices, legal regulations in the social protection and juvenile justice areas, and the needs and possibilities of social protection in Serbia, the preventive programme “OPTIMUS – Optimal Approach to Treatment and Integration of Youth in Conflict with the Community” has been developed. The programme aims to decrease antisocial behaviour, improve personal capacities and social competences, and improve integration into the community for children with behavioural problems. It is appropriate for the treatment of children and adolescents with more serious antisocial behaviour and from multiproblem families, but who do not have persistent forms of antisocial behaviour, severe mental disorders or substance dependence. The programme includes three forms of community treatment: workshops with youth, workshops with parents and family visits. Workshops with youth and family visits were implemented in practice and evaluated. The treatment group included 36 male adolescents aged 14 to 19 years and their families from three Belgrade municipalities. Evaluation by programme users and implementers showed that adolescents were better integrated into the community, while families showed improvement in overcoming adolescents’ problems and fulfilment of family members’ needs. Results of retests using the Socialisation Scales by Momirovic et al., completed by adolescents, and the Child Behaviour Checklist by Achenbach, completed by parents, showed a decrease in antisocial behaviour and an increase in pro-social skills.